Teaching training report at the School of Humanities - Miranda Gutiérrez, Eduardo Alexis; Herrera, Rosario (La Chorrera, Panamá : Centro Regional Universitario de Panamá Oeste, Vicerrectoría de Investigación y Postgrado, 2015)
Fulfilling objectives, in university education is a great challenge; it imposes specific demands, not only on scientific content but also on English Language content. Teaching must stimulate students to learn, to seek information and to critically synthesize information and knowledge, and also offers possibilities for applying their acquired skills. This means that a variety of teaching methods need to be applied. To define objectives for the whole educational program and for each individual course is essential and the objectives given should be acomplished actively by teacher, that is to say, by me, as well as by students. The objectives should not only focus on subject knowledge, but also on the skills to be developed. Students must become aware of what they need to learn to succeed, and teachers should refiect upon what and how to teach to best stimulate the learners, and how to evaluate them. It is essential to evaluate how well the objectives have been fuiflhled. The syllabus presented to the students must take into account four specific objectives that we will deal with later on. 1 think that this PracticumTraining course is designed to equip trainees who do not have previous teaching experience with he necesarry skills and knowledge in English language teaching to gain the experíence in Teaching English to Speakers of Other Languages, enabling them to begin a career as English Teachers to adults at University or at any higher eduaction level or atmosphere.
"Presented in partial fulfillment of the Requirements to obtain the Master´s Degree in Applied Linguistics". -- Página de título.
Keywords: INGLES -- ENSEÑANZA SUPERIOR; INGLES -- GRAMATICA; LINGUISTICA APLICADA; FORMACION PROFESIONAL DE MAESTROS; INGLES -- TESIS Y DISERTACIONES ACADEMICAS